Transparent subsidized agri‐product distribution during pandemics with reputation based PoA blockchain. (3rd February 2022) - Bala, Kirti; Kaur, Pankaj Deep
Summary: Technological advancements play a crucial role in agriculture sector aiming at eradicating numerous problems. These problems are intensified due to pandemics like delay overhead in the subsidized agri‐products supply chains. The existing technology‐based solutions are not readily adopted by stakeholders due to absence of trust. Blockchain can impart more transparency and trust in agri‐supply chains leading to fair pricing. The idea of using blockchain for financing processes in agriculture has resulted from the managerial pressure and fiscal scams which eventually aggravate the plight of farmers. Thus, a blockchain‐based subsidized agri‐products distribution (SAPD) is proposed. Blockchain has been optimized by a reputation‐based Proof‐of‐Authority (PoA) consensus algorithm. It has been implemented using Ethereum blockchain on AWS EC2 cloud. The smart contract is designed in solidity. Detailed performance evaluation has been conducted to compute cost and processing time that shows a substantial reduction in cost of managerial operations with respect to previous work by 41.65%. Finally, to assess the utility of SAPD system a qualitative user survey has been conducted. Managerial significance of system is reflected in memory space reduction by 85% in light clients and increase in transaction execution per second by 31% using reputation‐based PoA.